Sistem Informasi Raport Online Berbasis Web Pada SMK Negeri 1 Slawi - Wati, Fanny Fatma; Widodo, Andrian Eko; Sari, Ratna Kurnia (UNIVERSITAS RAHARJA, 2023)
The work system of teachers and staff of SMKN 1 Slawi still uses a conventional system that has the risk of errors in data input, besides that conventional data input also takes a long time to process. The design of the E-Raport Information System for SMK N 1 Slawi is a web-based information system created to facilitate and speed up teachers and staff in inputting data and assessing and evaluating students' learning from data input to printing report cards. The design of the E-Report Card Information System is expected to change the way teachers work from a conventional work system to a digital work system. In addition, the design of the e-report card information system aims to minimize errors in inputting data and student scores. The web-based E-Report Card Information System is designed using the SDLC (System Developmen Life Cyce) development system which carries out the research process using the waterfall method. Meanwhile, the software model carried out in the preparation of this research uses a programming model. The language used for this research is to discuss CSS programming, PHP, Java Script, HTML, Font Awesome, Data Tables, Boostrap and the databases used are MySQL and MariaDB databases